2012
DOI: 10.1080/02673037.2012.725833
|View full text |Cite
|
Sign up to set email alerts
|

Strategies forInSituHome Improvement in Romanian Large Housing Estates

Abstract: Socio-economic and physical change has visibly affected post-socialist cities, yet the state of decay of their inherited large housing estates has only deepened throughout the 1990s, despite of the change in tenure through IntroductionUnder the macro-economic constraints of post-communist restructuring since 1989, Eastern European governments have launched neo-liberal policies of large scale housing privatisation and overall state retreat from housing provision. Consequently, owner-occupation has reached over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 36 publications
1
37
0
1
Order By: Relevance
“…It is important to acknowledge that very different forces at play have resulted in different outcomes across countries and social groups, nonetheless the contrast between the apparent compliance of most flat-owners in the communist estates and the proactive agency of selfbuilders raises important questions, not least regarding their meanings of home. Some questions regarding residents" challenges to home improvement in Romania were addressed elsewhere (Soaita 2012, 2013, Pascariu and Stanescu 2003, the latter will be explored in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to acknowledge that very different forces at play have resulted in different outcomes across countries and social groups, nonetheless the contrast between the apparent compliance of most flat-owners in the communist estates and the proactive agency of selfbuilders raises important questions, not least regarding their meanings of home. Some questions regarding residents" challenges to home improvement in Romania were addressed elsewhere (Soaita 2012, 2013, Pascariu and Stanescu 2003, the latter will be explored in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Lux and Sunega (2014, 514) proposed -in a quite critical-realist vein -an explanation of path dependence framed under the "privatization trap" as "a trickle down mechanism" generating expectations of continued privatization in the newly built social housing and reinforcing already strong social norms of owner-occupation. Likewise, in-kind restitution of housing and land, and housing privatization have resulted in fragmented property rights with long-term consequences for how housing is developed and maintained (Górczyńska 2017;Lux, Cirman, and Sunega 2017;Soaita 2012;Vranic, Vasilevska, and Haas 2015). We anchor the idea of path-dependent change in the communist past by highlighting key differences across the political economies and forms of housing provisions across the communist states in the following section.…”
Section: The Ontological Depth Of Housing Quality: a Critical-realistmentioning
confidence: 99%
“…As the 1990s reforms of housing privatization and restitution are by now well-documented (Clapham et al 1996;Lowe and Tsenkova 2003), we will focus on the changes that have taken place since 2000. Economic growth and remittances have stimulated new housing construction throughout the region, stirring (self-built) suburbanization (Hirt 2008;Soaita 2013;Stanilov 2007), private regeneration of communist housing estates (Cirman, Mandič, and Zorić 2013;Soaita 2012;Vranic, Vasilevska, and Haas 2015) and gentrification in some cities (Górczyńska 2016;Kovács, Wiessner, and Zischner 2012).…”
Section: Mapping Post-communist Structural Changementioning
confidence: 99%
“…Orban (2006) looked into the evident difficulties with condominium management within the privatised social housing sector in Budapest, Hungary, a phenomenon that has also been studied in many other eastern European cities (Grover, Munro-Faure, & Solviev, 2002;Rabenhorst & Ignatova, 2009;Soaita, 2012). Using Olson's theory of collective action (Olson, 1965), Orban found that condominium size (measured in number of dwellings) is negatively associated with the cooperative potential of a building's residents.…”
Section: Literaturementioning
confidence: 99%